Trial of vitamin D supplementation to prevent asthma exacerbation in children - Krishnan, Elango; Ponnusamy, Venmugil; Sekar, Sathiya Priya (International Journal of Research in Medical Sciences, 2017)
Background: To assess the level of vitamin D in children with bronchial asthma and to study the effects of vitamin D supplementation in asthmatic children who had vitamin D deficiency in terms of asthma control test score and Number of exacerbations. Methods: This interventional study was conducted in Department of Paediatrics, KAPV Government medical college, Trichy, Tamil Nadu, India from September 2016 to February 2017. 96 asthmatic children of age group 5-12 years who attended outpatient department and admitted in ward for asthma exacerbation were selected. After assessing their Vitamin D level, Vitamin D supplementation given along with standard treatment for asthma. Outcomes measured were ACTS (Asthma control test score), number of emergency room visits, number of hospital admissions and reliever medication use. Results: Out of 96 children, 83 (86.4%) children had vitamin D deficiency. There was significant correlation between vitamin D level and absolute eosinophil count (p-value-0.037), asthma severity (p-value<0.001) and asthma control (p-value<0.001). Significant reduction in emergency room visits, (p-value<0.001) reliever medication use (p-value<0.001) and improvement in asthma control test score (p-value-0.008) occurs after vitamin D supplementation. Conclusions: There is a significant correlation between vitamin D level, asthma severity and its control. Asthma exacerbation in terms of emergency room visits and reliever medication use were further reduced by vitamin D supplementation.